Introduction to drug metabolism - GORDON GIBSON ,G; Skett,Paul ([S.l.] : Springer, 1996)
This introduction to the mechanisms by which the body metabolizes and excretes administered drugs is directed at advanced undergraduate biochemists, pharmacologists, pre-clinical medical strudents and advanced undergraduate/postgraduate toxicologists. The subject is approached from both biochemical and physiological angles. The examples of drug metabolism have been kept clinically relevant, so that the practical importance of the subject can be easily appreciated. The book contains a section of experimental procedures for setting up student practicals in drug metabolism.
Keywords: drugs,drug metabolism